What Words Bring to the Table: The Linguistic Anthropological Toolkit as Applied to the Study of Food. (May 2014) - Cavanaugh, Jillian R.; Riley, Kathleen C.; Jaffe, Alexandra; Jourdan, Christine; Karrebæk, Martha; Paugh, Amy
<x xml:space="preserve">Abstract</x> This article offers an introduction to the methods being developed by scholars interested in studying food and language as interrelated phenomena. First, we explore a few of the intriguing parallels that have inspired a number of researchers to study food and language simultaneously. Then, we look at how the study of language led each of us to the study of food and consider if and how the methods we have used for this new enterprise differ from linguistic anthropological methods used to study other cultural material. Finally, we expand upon the specific methods we have developed for studying how foodways and language use are intertwined. In passing, we note some of the new research terrains and theoretical questions that may be explored by interweaving food‐and‐language methodologies in these ways. This multiauthored article, which emerged from a roundtable at the 2013 American Anthropological Association Annual meeting on the same topic, has a dialogic structure that reflects the ongoing conversation in which we are engaged while also manifesting the unfinished nature of the project.